Creative Encounter : Festschrift for Herman Salinger - Phelps, Leland R.; Tilo Alt, A.; Phelps, Leland R.; Tilo Alt, A. (Chapel Hill The University of North Carolina Press, 1978)
A collection of thirteen essays by comparatists and Germanists published in celebration of the scholar and poet Herman Salinger. The essays range from Greek antiquity to the twentieth century$1 (Bfrom the Sophoclean "Electra" to Rilke. Two poems by Rudolf Hagelstange and Karl Krolow, Tabula Gratulatoria, and a bibliography of Herman Salinger's publications are also included in the volume. The contributors include: John Kunstmann, Helmut Rehder, Leland Phelps, Frank Borchardt, Eugene Falk. Haskell Block, Beda Allemann, James O'Flaherty, Tilo Alt, William Rey, George Schoolfield, and Hermann Weigand.s
National Endowment for the Humanities
Andrew W. Mellon Foundation
English
Keywords: Literature: history & criticism; German Studies; Literature